Regeneration of NCM622 from end-of-life lithium-ion battery cathode materials. Issue 2 (4th January 2023) - Gu, Shuai; He, Ting; Kong, Jiao; Fu, Tongtong; Guo, Zirui; Cui, Jingzhi; Chen, Zhihao
Abstract : The boom of the electric vehicles significantly aggravates the demand for lithium-ion batteries (LIBs), especially the ternary cathode materials, however, the majority of end-of-life LIBs on the market are batteries utilized in customer electronics. Abstract : The boom of the electric vehicle industry significantly aggravates the demand for lithium-ion batteries (LIBs), especially the ternary cathode materials, however, the majority of end-of-life (EOL) LIBs on the market are batteries utilized in customer electronics. Here, we utilized the mixed EOL LIBs from cell phones and laptops to manufacture the LiNi0.6 Co0.2 Mn0.2 O2 (NCM622) cathode material. A feasible, high efficiency (99.98% Co, 99.98% Ni, 99.99% Mn, and 99.99% Li), and ultra-fast leaching of EOL LIB cathodes was achieved. Thermodynamic calculations suggested that the coordination number, coordination species concentrations, and fractions have significant effects on the apparent activation energy and the equilibrium of the leaching reactions. The remanufactured NCM622 cathode material demonstrated a well-ordered layered hexagonal structure with a low Li + /Ni 2+ mixing ratio, which facilitated reliable reversible capacity, low polarization, high rate capabilities (163.8 mA h g −1 ), and capacity retention ratio (94.3%).